Dose- and application route-dependent effects of betahistine on behavioral recovery and neuroplasticity after acute unilateral labyrinthectomy in rats - Antons, Melissa; Lindner, Magdalena; Eilles, Eva; Günther, Lisa; Delker, Astrid; Branner, Christina; Krämer, Anja; Beck, Roswitha; Oos, Rosel; Wuehr, Max; Ziegler, Sibylle; Strupp, Michael; et al. (Frontiers in Neurology, 2023)
Introduction: Betahistine is widely used for the treatment of various vestibular disorders.However, the approved oral administration route and maximum daily dose are evidently not effective in clinical trials, possibly due to a major first-pass metabolism by monoamine oxidases (MAO). The current study aimed to test different application routes (i.v./s.c./p.o.), doses, and concurrent medication (with the MAO-B inhibitor selegiline) for their effects on behavioural recovery and cerebral target engagement following unilateral labyrinthectomy (UL) in the rat.Methods: Sixty rats were subjected to UL by transtympanic injection of bupivacaine/arsenilate and assigned to five treatment groups: i.v. low-dose betahistine (1mg/kg bid), i.v. high-dose betahistine (10mg/kg bid), p.o. betahistine (1mg/kg bid)/selegiline (1mg/kg once daily), s.c. betahistine (continuous release of 4.8 mg/d), and i.v. normal saline bid (sham treatment) (days 1-3 post UL, respectively). Behavioural testing of postural asymmetry, nystagmus, and mobility in an open field was performed seven times until day 30 post UL and paralleled by sequential cerebral [ 18 F]-FDG-µPET measurements. Results: Therapeutic effects of betahistine after UL differed in extent and time course and depended on the dose, application route, and selegiline co-medication: postural asymmetry was significantly reduced on 2-3 days post UL by i.v. high-dose and s.c. betahistine only. No changes were observed in the intensity of nystagmus across groups. Movement distance in the open field increased markedly by up to 5-fold from 2-30 days post UL in the s.c., i.v. highdose, and p.o. betahistine/selegiline group compared to sham treatment. [ 18 F]-FDG-µPET showed a dose-dependent rCGM increase in the ipsilesional vestibular nucleus until day 3 post UL for i.v. high-vs. low-dose betahistine and sham treatment, as well as for p.o. betahistine/selegiline and s.c. betahistine vs. sham treatment. From 1-30 days post UL, rCGM increased in the thalamus bilaterally for i.v. high-dose betahistine, s.c. betahistine, and p.o. betahistine/selegiline vs. saline treatment.Discussion: Betahistine has potential to augment the recovery of dynamic deficits after UL, if the administration protocol is optimized towards higher effective plasma levels. This may be achieved by higher doses, inhibition of MAO-based metabolism, or a parenteral route. In vivo imaging suggests a drug target engagement in central vestibular networks.